Project: Berita Fearure Pada Program “Jawa Tengah Hari Ini” di Stasiun TVRI Jawa Tengah (Posisi: Director dan Voice Over Talent) - Ridha Fadhila; Muhammad Bayu Widagdo; Yanuar Luqman (Interaksi Online, 2023)
TVRI Jawa Tengah is a public broadcasting institution tasked with broadcasting information with educational value to the public. As a form of responsibility in becoming a means of preserving culture and local wisdom values, TVRI Jawa Tengah has one of the news programs, namely Jawa Tengah Hari Ini. This program contains one of the Mini Feature segments which contains light news information. Feature itself is news coverage that is informative, educative, entertaining, convincing, and provides human values (human interest) so that it can make the sympathy or empathy of those watching it moved and not bound by time (timeless). This project is present to fill the Mini Feature segment with content that raises a big theme about culture in accordance with TVRI's duties as a public broadcasting institution. The big theme is divided into several categories including arts, tourism, culinary, history, and rituals/traditions. This project took place by producing 48 contents with an average duration of 5-7 minutes. This content was aired on TVRI Jawa Tengah Station in April-July 2022 and rebroadcast through the YouTube channel "Karbid TVRI". In its implementation, there are 4 main job desks in the pre-production, production, and post-production processes: producer, director, reporter, cameraman.